The Utilization of Seaweed (Eucheuma cottoni) to Increase Iodine and Dietary Fiber Contents of Jam and Dodol - Made Astawan; Sutrisno Koswara; Fanie Herdiani (Jurnal Teknologi dan Industri Pangan, 2004)
Indonesia is known as a country rich in species of seaweed. The most important components of seaweed are iodine and dietary fiber. Eucheuma cottoni is one species of seaweed that can be used as a source of iodine and dietary fiber. Iodine deficiency can cause several diseases also known as IDD (Iodine Deficiency Disorder), while deficiency of dietary fiber can cause some degenerative diseases. This research is taken to develop the utilization of Eucheuma cottoni as an ingredient in the making of jam and “dodol” (Indonesian traditional snack food). The best ratio of seaweed and sugar for jam production was 37:63, while the best ratio of seaweed and glutinous flour in making dodol was 5:2. The addition of seaweed on jam and dodol formula increased their iodine and dietary fiber contents. The iodine content of jam and dodol was 17.79 and 19.57 Ã‚Âµg/g, respectively. The dietary fiber content of jam and dodol was 5.75 and 5.63%, respectively. Key words : Disorder, dietary fiber, dodol, jam, seaweed